Rationing and Exchange Control in British War Finance - Holden, Grenville (Quarterly Journal of Economics, 1940)
Two major objectives of British policy which can and should be implemented by the same regulatory technique, 171.— I. The non-quantitative approach: burdens likely to be heavy, 172; and require maximizing of resources 173.— The Economist's educational campaign, 174.— Hansen's view, 176.— The best sterling exchange rate for the duration of the war would be nearer $5.00 than $4.00.— Theoretical justification of this position, 177.— II. The statistical approach: points to be established, 182.— Volume of British exports likely to fall, 183.— Britain's foreign markets will not be reduced by war, and may be increased, 185.— What depreciation is costing Britain, 186.— Behavior of British prices, 190.— III. Summary of Britain's wartime economic problems, 196.